TRANSFORMASI DIGITAL UMKM DI WILAYAH CIREBON DAN SOMALIA: KOLABORASI DAN INOVASI UNTUK PENGEMBANGAN PASAR GLOBAL - Nur Hajijah, Sitta; Fariza, Muthia; Lukita, Chandra; Amroni, Amroni; Nurhana Dhea Praadha Gitama, Gytha; Kartika, Ika; Dwi Kartika, Viar; Triantika, Nova (Jurnal Masyarakat Indonesia (Jumas), 2025)
Community Service Activities (PkM) entitled "Digital Transformation of MSMEs in the Cirebon and Somalia Regions: Collaboration and Innovation for Global Market Development" is a collaborative initiative involving Catur Insan Cendekia University (UCIC) Cirebon, Department of Cooperatives , Small, Medium Enterprises, Trade and Industry (DKUKMPP) Cirebon City, and the African Institute for Multidisciplinary Studies (AIMS) Somalia. This program aims to support Micro, Small and Medium Enterprises (MSMEs) in utilizing digital technology to increase competitiveness and market penetration at the global level. The methods used include intensive training, technical assistance, and interactive discussions conducted in a hybrid manner, utilizing digital platforms to reach participants from both countries. The focus of activities is the application of digital marketing technology, social media optimization, and effective e-commerce management. This activity also introduced cross-border collaboration strategies as an effort to expand business networks between MSMEs in Cirebon and Somalia. The results of this program show an increase in the ability of MSME players to use digital technology, with several participants succeeding in increasing the visibility of their products in the international market. Apart from that, business collaboration opportunities were created between MSMEs in Cirebon and Somalia through digital platforms initiated during the program. This collaboration is also a clear example of how synergy between educational institutions, government and international organizations can create a positive impact on empowering MSMEs in the era of globalization.